Impact of immunogenicity on efficacy and tolerability of tumour necrosis factor inhibitors: pooled analysis of biosimilar studies in rheumatoid arthritis. (2nd September 2020) - Emery, P; Suh, C-H; Weinblatt, ME; Smolen, JS; Keystone, EC; Genovese, M; Vencovsky, J; Kay, J; Hong, E; Baek, Y; Ghil, J
Abstract : Objective : SB4, SB2, and SB5 are biosimilars of etanercept (ETN), infliximab (INF), and adalimumab (ADA), respectively. This pooled analysis evaluated the immunogenicity of these treatments across three phase III randomized controlled trials of patients with rheumatoid arthritis (RA). Methods : Patients had to have at least one anti-drug antibody (ADAb) assessment up to the time of the primary endpoint from each study (week 24 in SB4 and SB5 studies; week 30 in SB2 study). The effect of ADAbs on American College of Rheumatology 20% (ACR20) response and the incidences of injection-site reactions (ISRs)/infusion-related reactions (IRRs) were evaluated. Results : The study included 1709 patients. The cumulative incidences of ADAbs were 30.3% in the all-treatments-combined group, 29.1% in the biosimilars combined group, and 31.5% in the reference products combined group. ACR20 response rates were significantly lower in ADAb-positive patients in the all-treatments-combined [odds ratio (95% confidence interval) 1.77 (1.37, 2.27), p < 0.0001], biosimilars combined [2.24 (1.53, 3.30), p < 0.0001], and reference products combined [1.49 (1.06, 2.09), p = 0.0225] groups. ADAb-positive patients also had a higher likelihood of developing ISRs/IRRs in the all-treatments-combined group [0.56 (0.31, 1.01), p = 0.0550], predominantly due to the results observed with SB2 + INF combined rather than with SB4 + ETN or SB5 + ADA combined. Conclusion : In this pooled analysis, ADAbs were associated with reduced efficacy in patients with RA treated with biosimilars (SB4, SB2, and SB5) or their reference products (ETN, INF, and ADA). ADAbs were associated with an increased incidence of ISRs/IRRs in those treated with SB2 + INF. Clinical trial registration numbers: NCT01936181 (SB2 study), NCT01895309 (SB4 study), and NCT02167139 (SB5 study).